SP0068 Molecular targets for therapy in liver fibrosis. (23rd January 2014) - Brenner, D.
Abstract : One of the key issues for identifying new targets for the treatment of liver fibrosis is the identification of the cell producing the fibrous scar. Although clinical and experimental research clearly identifies that myofibroblasts are the source of the extracellular matrix proteins, the origin of these myofibroblasts is still unclear. However, using novel transgenetic mice to mark the cell fate of hepatic cells, progressively more studies support the concept that quiescent hepatic stellate cells become activated during fibrogenesis to become the major source of the myofibroblasts responsible for the fibrous scar. Therefore, understanding the activation process of the hepatic stellate cell as well as developing techniques to target drug delivery to stellate cells has become the focus of current research. Several signaling molecules and transcription factors have been identified as critical in determining the quiescent versus activated phenotype of the hepatic stellate cells. NFκB is the best studied transcription factor that is required for stellate cell activation. The activity of NFκB is continuously elevated in activated hepatic stellate cells, and NFκB activity is required for the survival of activated stellate cells. Profibrogenic angiotensin II leads to phosphorylation of the p65 subunit of NFκB at its Ser536 residue. General inhibitors of NFκB including gliotoxin and sulfasalazine are antifibrotic in rodent models of hepatic fibrosis. Furthermore, a specific peptide mimetic that competitively inhibits Ser536 phosphorylation inhibits NFκB activity and fibrosis. PPAR-g is a critical transcription factor required to maintain stellate cells in a quiescent state or to convert cultured activated stellate cells back to a quiescent phenotype. Two different signaling pathways Wnt and Shh both act on the PPAR-g gene to induce epigenetic repression. Therefore, blocking the Wnt or Shh pathways result in increased expression of PPAR-g and reversion to a quiescent phenotype. In addition, PPAR-d agonists prevent hepatic fibrosis in experimental rodent models. Many fibrogenic agonists such as PDGF, leptin, and angiotensin II, mediate their profibrogenic affects on hepatic stellate cells by activating NADPH oxidase to produce reactive oxygen species. Therefore, many studies have used antioxidants to block rodent models of liver fibrosis. However, perhaps a more effective drug might be pirfenidone. This drug has both antioxidant and anti-inflammatory affects. Pirfenidone blocks many of the profibrogenic activities of activated hepatic stellate cells. Since this drug has already been approved for treatment in patients, it appears to be ready for a clinical trial in the therapy of liver fibrosis. If activated hepatic stellate cells are the key cell synthesizing the fibrous scar, then developing drug delivery systems to target these cells specifically would be a key breakthrough in anti-fibrotic therapy. Three drug delivery systems have been developed to target hepatic stellate cells in rodent models of hepatic fibrosis. To target the mannose-6-phosphate/insulin-like growth factor 2 receptor (M6P/IGF-2R) drugs are coupled to mannose-6-phosphate human serum albumin which is taken up specifically in activated HSCs through this receptor. Recently, a rho kinase inhibitor and an angiotensin receptor blocker have been conjugated to M6PHSA and were used successfully in rodent models to block hepatic fibrosis. The PDGF receptor is also unregulated on activated hepatic stellate cells, and these cells are believed to be the only cell in the liver expressing this receptor. Interferon gamma was conjugated to a peptide that binds the PDGF beta receptor. Most recently, Vitamin A coupled liposome have been used to carry siRNA to block a fibrogenic gene. The concept is that the activated hepatic stellate cells will take up the vitamin A liposome containing the siRNA by receptor mediated uptake bound to retinol binding protein. This technique has been used in culture and in vivo to direct the siRNA for the collagen chaperone p47 into activated hepatic stellate cells resulting in decreased hepatic fibrosis. Disclosure of Interest: None Declared